Caminhos para socioeconomias alternativas em áreas rurais: elementos de agroecologia e economia solidária do Assentamento Santa Rita, Aratuba - CE - Cunha, Francisco Eduardo de Oliveira (2013)
It has been observed in recent decades that the capitalist mode of production has expanded in rural places (habitat of origin ) in unprecedented greed, under the aegis of the so called Green Revolution. Referred revolution in the field have contributed to the modernization of agriculture, implementing practices of monoculture, intensive use of chemicals in soil fertilization and pest control, genetic improvements, among other actions. However, such changes have contributed for the devastation of cropland sharp, and the allocation of local ecosystems and also the health of farmers and consumers of this "new type" of food. Moreover, this relentless pursuit of economic growth in rural places, it was found that two entities belonging to the same complex living system and were put into opposing sides: the man (organized in the economy and society) - and nature. There is therefore a clear perception of a critical and alarming that relate, especially when faced with environmental degradation and rampant use of natural resources in order to meet the growing insatiable and unsustainable model of capitalist accumulation. Faced with this scenario over crisis - the environment - such research is launched to perform a descriptive analysis of the experiences of Agroecology and Solidarity Economy of smallholders nesting Santa Rita, located in the municipality of Aratuba within the Environmental Protection Place of Sierra Baturite in the state of Ceará, seeking to legitimize and find empirical evidence of alternative ways possible , in view of a more harmonious relationship between the economy and nature, from a theoretical approach of Ecological Economics. In view of present and describe such evidence, we have implemented the construction of an index that seek to gauge elements agroecology and solidarity economy practices in agricultural settlement studied , which is called iecosol in order to provide insight to the an analysis whose agenda in predominantly qualitative aspects. Finally, the results obtained in iecosol, it was observed that even before the difficulties faced by small producers in the statement of the elements of alternative economies, such experiences have contributed to the debate and discussion about different feasible production rationality, which recognizes nature as limiting economic relations, especially in rural places, which still exhibit characteristics that favor the practice of relations between these men and with nature, in a more harmonious and less degrading.